Impact of the COVID-19 pandemic on sedentary behavior and physical activity level of state school teachers in a municipality in the North of Minas Gerais (Research, Society and Development, 2021)
In the face of the pandemic context by COVID-19, the practice of social isolation has caused some impacts on the lives of teachers, related to the use of digital technologies, added to their conjugal, maternal and domestic lives and so many other attributions that are given to them. Additionally, causing an increase in physical inactivity and physical inactivity. Thus, this study aims to assess the impact of the COVID-19 pandemic on the sedentary behavior and level of physical activity of teachers from the state school system in Monte Azul-Minas Gerais. A descriptive cross-sectional and quantitative study was carried out. Participants answered online questionnaires through Google Forms, sent via @Whatsapp. A Chi-square test was used to assess associations between sedentary behavior and the level of physical activity before and during the pandemic period. The sample consisted of 72 teachers. Teachers' sedentary behavior increased significantly (p = 0.000) during social isolation. While the practice of physical activity showed an increase, it was not significant (p = 0.182). Despite the increase, the prevalence of teachers who do not practice enough physical activity is high, ranging from 63.9% before and 55.6% during social isolation. It is concluded that social isolation by the pandemic COVID-19 resulted in a significant increase in sedentary behavior is a high prevalence of insufficient physical activity among teachers in the state school system. In this way, the study has practical implications for thinking about forms of intervention for this population in order to encourage the practice of physical activity and reduce sitting time during periods of social distance.